GENERATION Z'S MULTITASKING LEARNING STYLE AND ITS IMPLICATIONS FOR THE DEVELOPMENT OF INFORMATION SERVICE TECHNOLOGY IN LIBRARIES - Evriza, Eka; Ridwan, Muhammad (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
Generation Z is known for its highly multitasking behavior in learning and information-seeking processes. The tendency to access multiple sources simultaneously through digital devices characterizes their learning style. In the context of libraries, this multitasking behavior presents specific challenges, particularly in designing information services that meet their needs. This article is a literature review that aims to analyze the relationship between Generation Z’s multitasking learning style and the development of technology-based library information services. The review draws on recent studies discussing Generation Z characteristics, digital multitasking behavior, and technological advancements in library environments. The findings indicate that library technologies such as online catalogs, access to e-resources, flexible learning spaces, and social media integration play a vital role in meeting the expectations of this generation. However, multitasking may also reduce the effectiveness of information processing, necessitating adaptive, personalized service designs that support focused learning. This review recommends that libraries develop technology-based strategies that account for the cognitive behavior of Generation Z users, in order to create a more effective and relevant learning experience. This study offers a theoretical contribution to understanding the link between young users’ digital behavior and innovation in library information services.